2007
DOI: 10.1007/s00405-007-0366-1
|View full text |Cite
|
Sign up to set email alerts
|

Sleep nasendoscopy: a 10-year retrospective audit study

Abstract: Sleep nasendoscopy was conceived at the Royal National Throat, Nose and Ear Hospital, UK in 1991, and has remained fully implemented in patient selection for targeted treatment of the spectrum of sleep-disordered breathing. The senior authors (B.T.K. and P.B.) have been performing sleep nasendoscopy together for over 10 years, and we look back at their decade's experience. A retrospective audit study based on case notes was performed over a 10-year period (1995-2005) in a tertiary-referral practice setting. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
90
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 19 publications
(1 reference statement)
2
90
1
1
Order By: Relevance
“…Although DISE has been shown to be reliable, some critics of the technique suggest that sedative-induced sleep only provides a small window into the complex and variable patterns of natural sleep. [25][26][27] The present study demonstrates a more dynamic approach to DISE. The surgeon actively manipulated the upper airway with a NPT to better understand the interplay of the different sites of obstruction.…”
Section: Discussionmentioning
confidence: 61%
“…Although DISE has been shown to be reliable, some critics of the technique suggest that sedative-induced sleep only provides a small window into the complex and variable patterns of natural sleep. [25][26][27] The present study demonstrates a more dynamic approach to DISE. The surgeon actively manipulated the upper airway with a NPT to better understand the interplay of the different sites of obstruction.…”
Section: Discussionmentioning
confidence: 61%
“…[2][3][4] Various sedation methods have been used to allow for the performance of DISE. Roblin introduced target-controlled infusion (TCI) of propofol to DISE to allow for better control of the sedation level.…”
mentioning
confidence: 99%
“…Accurately identifying the main source of snoring sound is important for surgical success [9]. DISN was first described by Croft and Pringle [10] in 1991, and this procedure allows a direct visualization of the sites of vibration or obstruction in a sleeping patient.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol and midazolam are the two main drugs which are commonly used in DISN [3,9,21]. Kotecha et al [9] found that the titrated administration of propofol combined with midazolam worked well in DISN. However, the disadvantage of midazolam is its longer elimination and respiratory depression effect [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation